Role of perifollicular Doppler blood flow in predicting cycle response in infertile women with genital tuberculosis undergoing in vitro fertilization/intracytoplasmic sperm injection - Neena Malhotra; Anupama Bahadur; Neeta Singh; Mani Kalaivani; Suneeta Mittal (Wolters Kluwer Medknow Publications, 2014)
Objective: This study was evaluated the role of perifollicular Doppler blood flow in predicting cycle response in women with and without genital tuberculosis (TB) undergoing in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) cycles. Materials and Methods: This prospective observational study was performed on 254 women undergoing IVF for tubal factor infertility in the assisted reproductive unit. Perifollicular Doppler blood flows were assessed in dominant follicles >16 mm before oocyte recovery in patients with and without genital TB. Results: A positive correlation was found between estradiol on the day of human chorionic gonadotropin (r = 0.15, P = 0.05), number of oocytes retrieved (r = 0.25, P = 0.001), MII (r = 0.24, P = 0.001), day 1 2PN (r = 0.16, P = 0.04), number of embryos (r = 0.16, P = 0.04) and blood flow in patients without genital TB. A trend of having poor ovarian blood flow was observed in patients with genital TB when compared with those without the disease (P > 0.001). Conclusion: In our study, the perifollicular blood flow (PFBF) provided a favorable prediction on the quantity of oocytes retrieved, MII, day 1 2PN and number of embryos but did not show any significant statistical difference in other outcome variables including fertilization or cleavage rate in women with or without genital TB undergoing IVF/ICSI cycles. Hence PFBF has the potential to be used as a simple and non-invasive surrogate marker of capillary blood flow around recruitable follicles to predict response to ovarian stimulation and cycle outcome.